การตั้งราคาของสัญญาการประกันภัยต่อกรณีเกิดภัยพิบัติขนาดใหญ่สำหรับการประกันภัยชีวิต - จิราธร อำไพวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The aims of this research is to propose suitable method to calculation premium rate of catastrophe cover are reinsurance. The development of the model catastrophe of Strickler (1960) to get a new model that’s offers the premium rate of catastrophe excess of loss cover. The new model has a cost of claim that depend on various factors such as catastrophe rate of the number of death or lost and the number of claim using statistical method to observe the distribution of parameters and the Peaks Over Threshold theory to estimate the number of death or lost of each catastrophe. In this study using data of the number of death or lost from Swiss Reinsurance and Department of Disaster Prevention and Mitigation. The information of those who death and lost in a foreign country and in Thailand since the years 2002-2008, which research has found that the number of death or lost in a foreign country in case of disaster at least 20 lives and one of Thailand with the number of death or lost of at least 4 lives will result in the distribution of damage to a Generalized Pareto Distribution. The distribution is consistent with the Peaks Over Threshold theory. The above result make this research to calculate the premium rate in case of the catastrophe, depending on factors of cost of damage from catastrophe and sensitivity analysis in other factor, the expected of the cost and standard deviation of the cost affect the price.